Research on the Establishment and Development Strategy of Calligraphy Characteristic School - Liu, Pei (Advances in Social Sciences Research Journal, 2022)
Calligraphy art is an excellent traditional treasure of China. For Chinese people, calligraphy education is not only the teaching of Chinese character writing skills, but also the cultivation of Chinese culture. It is also the process of experiencing and practicing the rules of square and round, cultivating self-cultivation, aesthetic perception and other spirits in the writing practice. Carrying out characteristic construction reform in schools is an important way to achieve quality education, and creating calligraphy characteristic schools is also an important part of school characteristic construction. The establishment of calligraphy characteristic schools can not only improve students' traditional cultural accomplishment, cultivate their moral sentiments, and cultivate their recognition of the excellent traditional culture of the Chinese nation and national spirit; Moreover, it can promote the development of schools, balance educational resources and promote educational equity. This paper will take school A in Tianfu New District, Chengdu, Sichuan Province, China as an example, sort out the construction and development of its calligraphy characteristic schools, refine and form characteristic, effective and referential calligraphy education experience, explore effective strategies, provide strong support for the construction and development of calligraphy education characteristic schools, form templates and paradigms, and further improve the comprehensive quality of calligraphy education characteristic schools as a whole, Promote the comprehensive popularization and high-quality development of calligraphy education.